2016
DOI: 10.3916/c48-2016-10
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of handwriting and computer typing in note-taking by university students

Abstract: Taking notes is a common strategy among higher education students, and has been found to affect their academic performance. Nowadays, however, the use of computers is replacing the traditional pencil-and-paper methodology. The present study aims to identify the advantages and disadvantages associated with the use of computer (typing) and pencil-and-paper (handwriting) for taking notes by college students. A total of 251 social and health science students participated in the study. Two experimental conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
15
0
5
Order By: Relevance
“…Frangou et al (2018) showed that the recall performance of participants half an hour and a week after the experiment resulted in a better performance with longhand copying than when it was done on a computer. Aragón-Mendizábal, et al (2016) also found that students were less able to recognize of word lists with a typed recall. They suggested that because typing is faster than handwriting, students process more information which is therefore less integrated in memory.…”
Section: Experiments 2a: Effect Of Typing On Short-term Recallmentioning
confidence: 91%
See 1 more Smart Citation
“…Frangou et al (2018) showed that the recall performance of participants half an hour and a week after the experiment resulted in a better performance with longhand copying than when it was done on a computer. Aragón-Mendizábal, et al (2016) also found that students were less able to recognize of word lists with a typed recall. They suggested that because typing is faster than handwriting, students process more information which is therefore less integrated in memory.…”
Section: Experiments 2a: Effect Of Typing On Short-term Recallmentioning
confidence: 91%
“…With more verbatim strategies, students would, on one hand, tend to encode information verbally and, on another hand, would process it at less deep levels (Aragón-Mendizábal et al, 2016;Luo et al, 2018). The effects on achievement of using a computer for taking notes therefore appear to depend on students' strategies for taking and reviewing notes, as well as on the format of the information presented to students.…”
Section: Introduction: Writing With Computersmentioning
confidence: 99%
“…Toutefois, le fait d'écrire sans comprendre ne permet pas à l'apprenante ou à l'apprenant de prendre des notes efficaces, c'est-à-dire des notes dans lesquelles les informations pertinentes sont organisées, hiérarchisées et liées entre elles (Williams et Eggert, 2002). De plus, les informations ne sont traitées que superficiellement et ne sont donc pas encodées dans la mémoire à long terme (Aragón-Mendizábal, Delgado-Casas, Navarro-Guzmán, Menacho-Jiménez et Romero-Oliva, 2016). Moins populaire, l'autre stratégie, qui consiste à prioriser la compréhension au détriment de la transcription, comporte elle aussi ses avantages et ses inconvénients.…”
Section: Pour Quelles Stratégies Les Apprenantes Et Les Apprenants Opunclassified
“…Moins populaire, l'autre stratégie, qui consiste à prioriser la compréhension au détriment de la transcription, comporte elle aussi ses avantages et ses inconvénients. En effet, lorsque les apprenantes et les apprenants se concentrent sur la compréhension au détriment de la transcription, ils traitent les informations plus profondément, c'est-à-dire qu'ils les encodent dans leur mémoire à long terme (Aragón-Mendizábal et al, 2016). Cependant, n'ayant pas constitué une mémoire externe fiable par la PDN, ils s'exposent à l'oubli de 80 % des informations entendues (Ozbay, 2005 cité dans Tahir, Tuncay, Ibrahim et Burak, 2013).…”
Section: Pour Quelles Stratégies Les Apprenantes Et Les Apprenants Opunclassified
“…Cabe destacar otro elemento de especial interés en el estado de la cuestión: la carencia de estudios en los que se recoja información sobre casos en contextos reales. Habitualmente, las experiencias se llevan a cabo a través de diseños específicos que recopilan datos aportados en experiencias aisladas del contexto académico real, basados en el recuerdo de palabras, secuencias o experimentos propios del ámbito de la psicometría (Aragón Mendizábal et al, 2016;Beck, 2014;Muñoz y Gómez, 2005).…”
Section: Introductionunclassified